2010
DOI: 10.1111/j.1551-6709.2010.01124.x
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Adaptation to Performance Objectives in a Dual‐Task Setting

Abstract: How do people interleave attention when multitasking? One dominant account is that the completion of a subtask serves as a cue to switch tasks. But what happens if switching solely at subtask boundaries led to poor performance? We report a study in which participants manually dialed a UK-style telephone number while driving a simulated vehicle. If the driver were to exclusively return his or her attention to driving after completing a subtask (i.e., using the single break in the xxxxxxxxxxx representational st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 28 publications
5
72
1
Order By: Relevance
“…However, the relationship in real traffic between lane deviation and crash risk is unknown, whereas there is a wealth of evidence of the more direct association between crash risk and long off road glances (Liang et al, 2012). It seems that in general, drivers do not try to optimize their lane position while multitasking and some lateral deviation is allowed even if the driving is prioritized (Janssen and Brumby, 2010). Keeping the own lane seems to be a sufficient and more critical goal than keeping an optimal lane position at all times, which is why we focus on glance metrics here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the relationship in real traffic between lane deviation and crash risk is unknown, whereas there is a wealth of evidence of the more direct association between crash risk and long off road glances (Liang et al, 2012). It seems that in general, drivers do not try to optimize their lane position while multitasking and some lateral deviation is allowed even if the driving is prioritized (Janssen and Brumby, 2010). Keeping the own lane seems to be a sufficient and more critical goal than keeping an optimal lane position at all times, which is why we focus on glance metrics here.…”
Section: Discussionmentioning
confidence: 99%
“…Janssen and Brumby (2010) have shown that people sometimes strategically control the allocation of attention in multitasking to meet specific performance criteria. For our purposes, for example, one might imagine strategic tradeoffs between stable driving and finishing a screen by a slightly longer in-car glance than the current time limit would allow, as discussed above.…”
Section: Limitations and Further Researchmentioning
confidence: 99%
“…In the domain of driving, multiple studies have looked at how drivers interleave nondriving, secondary tasks with driving. A common strategy is to wait for 'natural breakpoints' in the task to switch attention [11,12,26,27,28,48]; for example, Iqbal et al showed that drivers chunked a task of providing directions while driving into multiple steps and reoriented to driving at the boundaries between chunks [26]. There are many advantages of interleaving at natural breakpoints: it reduces mental workload [3,49] as it reduces information that needs to be maintained in memory [7], it frees mental resources such as visual attention for other tasks [50,55], it reduces stress [4], it reduces the time needed for later task resumption (cf.…”
Section: Managing Multitasking During Drivingmentioning
confidence: 99%
“…We therefore also included conditions in which drivers performed non-driving tasks. As the structure of the task can also impact when drivers look at the road [12,27,28], we used two tasks. Half the drivers performed a video transcription task while the other half performed a calendar task.…”
Section: Non-driving Tasksmentioning
confidence: 99%
“…For example, people who dial a phone while driving have to take moments to reexamine the road and adjust their course during interruptions [9]. In the case of microtasking, one might imagine the repeated sense-making that workers may have to do as they interleave and interrupt different varieties of tasks.…”
Section: Related Workmentioning
confidence: 99%